Analysis of the game statistics of the top eight teams at the European and World Championships 2020/24 in men’s water polo - Marković Vladan; Timotijevic Diana; Ahmetovic Zlatko; Milošević Miloš (Biomedical Human Kinetics, 2025)
Study aim: The aim of this study was to examine statistical parameters and determine which had the greatest influence on the final score at the European and World Championships in the period of 2020-2024.